TINJAUAN HAM TERHADAP ANAK BERKEBUTUHAN KHUSUS DALAM KESETARAAN PENDIDIKAN - Sucipto, Malakh Joy Barak; Ruslie, Ahmad Sholikhin (LPPM Universitas Bina Bangsa, 2024)
Education has a central role in pursuing social welfare and fulfilling human rights. The right to education is considered an important right, and education is considered the main prerequisite for starting other basic rights. Participating in social and cultural life, pursuing knowledge, and accessing higher education depend on understanding and increasing the minimum level of education. However, when talking about children with special needs, such as children with physical disabilities, challenges arise due to the education system which tends to separate educational institutions based on the type of disability. Segregated education models such as SLB for the Blind, SLB for the Deaf, and SLB for the Intellectually Impaired create problems. This exclusivity in education hinders the opportunity for children with special needs to receive an education equal to other children. Therefore, the concept of inclusive education emerged as an alternative that is expected to be able to overcome this problem. Inclusive education emphasizes the acceptance of all children in a regular educational environment regardless of their abilities or shortcomings. However, the implementation of inclusive education is still faced with a number of obstacles. These obstacles include the limited number of inclusive schools, lack of resources and training for teachers who can deal with the diverse needs of students, as well as discriminatory attitudes and treatment that can occur in the educational environment. In a legal context, Law Number 35 of 2014 concerning child protection in Indonesia emphasizes the right of every child to live, grow, develop and be protected from violence and discrimination. In terms of inclusive education, this shows the need for a friendly educational environment for children with special needs. The importance of inclusive education and the need to understand the rights of every child in education is reflected in the basic normative descriptions that underline equality of rights. This description leads to further explanation of the inclusive education model which is non-discriminatory and accommodates the needs of all children regardless of their background or abilities